Ten simple rules for managing laboratory information. - Casey-Tyler Berezin; Luis U Aguilera; Sonja Billerbeck; Philip E Bourne; Douglas Densmore; Paul Freemont; Thomas E Gorochowski; Sarah I Hernandez; Nathan J Hillson; Connor R King; Michael Köpke; Shuyi Ma; et al. (PLoS Computational Biology, 2023)
Information is the cornerstone of research, from experimental (meta)data and computational processes to complex inventories of reagents and equipment. These 10 simple rules discuss best practices for leveraging laboratory information management systems to transform this large information load into useful scientific findings.